No Independent Association of Circulating Fetuin-A with Insulin Sensitivity in Young Women - Reif, Sabrina; Moschko, Sarah; Gar, Christina; Ferrari, Uta; Hesse, Nina; Sommer, Nora N.; Seißler, Jochen; Lechner, Andreas (Hormone and Metabolic Research, 2020)
Animal data link high circulating fetuin-A to low insulin sensitivity and observational studies identify the hepatokine as a marker of future incident type 2 diabetes mellitus in humans. However, a recent, well-powered Mendelian randomization study finds no causal role. We therefore tested in a deeply-phenotyped human cohort if circulating fetuin-A correlates independently with insulin sensitivity and how it relates to the metabolic syndrome and ectopic fat deposition. We analyzed data from 290 young women with and without recent gestational diabetes mellitus. We found that circulating fetuin-A correlates inversely with insulin sensitivity in univariate analyses, but that this correlation is lost after adjustment for markers of the metabolic syndrome and of fatty liver. Additionally, we investigated which fat compartment associates most strongly with circulating fetuin-A. In whole body MRI data from a subcohort of 152 women, this was liver fat content. We conclude that high circulating fetuin-A occurs as part of the metabolic syndrome in young women and associates most strongly with liver fat content. Its close link to the metabolic syndrome may also cause the inverse correlation of circulating fetuin-A with insulin sensitivity as we found no independent association.
Keywords: type 2 diabetes; metabolic syndrome; non-alcoholic fatty liver disease; mineral metabolism